Ways of forming the professional competences of the courses of the psychological profile in the process of training - Stadnik, А. V.; Riutin, V. V.; Mirshuk, О. E.; Prokopenko, Yu. О. (Honor and Law, 2019)
The ways of formation of professional competencies of cadets of psychological profile in the process of study are considered. The concept of "competence", "competence approach" is analyzed and directions of implementation of the competent approach to the process of psychological training of specialists-psychologists are singled out. Are offered directions of formation of professional competence of cadets of psychological profile in the process of training.